The Janus effect: Contradictory demands placed on the academic chairperson - Pienaar, J W; Cilliers, F (South African Journal of Higher Education, 2016)
The purpose of this paper is to gain a deeper understanding of the multidimensional nature and complexity of the challenges academic chairpersons appointed at institutions of higher learning experience. A qualitative research approach was chosen to gain a comprehensive understanding of the phenomenon under investigation by means of a focus group of 24 academic chairpersons. The findings indicate that academic chairpersons are inundated with responsibilities. They have to find a balance between the various roles, responsibilities and tasks originating from two opposing roles – that of scholar versus that of administrator/manager/leader – forced into one, while lacking the necessary administrative/managerial/leadership experience, skills and knowledge for their role as managers. This study provides higher education institutions and role-players responsible for the appointment, support and development of academic chairpersons with the evidence required to substantiate the necessity of redesigning this role.